Adherence factors to hypertension treatment in primary care services - Solis, Aicardo; Bergonzoli-Peláez, Gustavo; Contreras-Rengifo, Adolfo (Universidad y Salud, 2021)
Introduction: In 2008, uncontrolled hypertensive arterial disease (UHAD) was associated with a high cardiovascular mortality that caused 9.4 million deaths and 7% of the disease burden expressed as Disability-Adjusted Life Years (DALYs). The reasons why 50% of the patients treated in primary care facilities in Colombia do not adhere to UHAD treatment are unknown. Objective: To identify factors associated with UHAD treatment adherence in a Public Health Care institution from a Colombian city. Materials and methods: A case-control study with 75 cases and 75 controls randomly selected from a patient database of the arterial hypertension control program. Results: Being older than 50 years was the only factor associated with lack of adherence to treatment. Participants who were 50-59 (OR=3.18; IC95% 1.01-10.00) and 60-69 (OR=3.70; IC95% 1.17-11.60) are less likely to adhere to treatment. Conclusions: Patients who are 50-69 years old had the highest probability of non-adherence to UHAD treatment. Follow-up measures are necessary to improve this figure.